Interaction-based coding of scaffolding processes. (April 2018) - Hermkes, Rico; Mach, Hanna; Minnameier, Gerhard
Abstract: In this article, we present a methodology for measuring scaffolding in small group classroom settings. We have investigated scaffolding by analysing teacher-student-interactions and developed an instrument to code student level of attainment and teacher strength of intervention as the relevant student and teacher variables. For the construction of interaction patterns the coded variables were related to each other. In order to assess the resulting interaction patterns for scaffolding quality, we devised rules based on the contingent shift principle. The analyses show that our methodology is reliable and valid, and that it is effective for discerning contingent from non-contingent interaction patterns. Furthermore, our fine-grained methodology allows us to identify and locate crucial points in the teacher's supporting behaviour that make for contingent or non-contingent scaffolding. Implications for the assessment of instructional quality as well as for teacher education and professionalism are discussed. Highlights: Scaffolding as "tailored support" is assumed to be correlated with learning outcomes. Process analyses of interactions are necessary to examine scaffolding. Teacher-student-interactions are investigated in a video study. We analysed interaction patterns using the Contingent-Shift-Principle. We can discern contingent from non-contingent patterns in a reliable and valid way.